2020
DOI: 10.1155/2020/7435260
|View full text |Cite|
|
Sign up to set email alerts
|

An Immunohistochemical Study of the Increase in Antioxidant Capacity of Corneal Epithelial Cells by Molecular Hydrogen, Leading to the Suppression of Alkali-Induced Oxidative Stress

Abstract: Corneal alkali burns are potentially blinding injuries. Alkali induces oxidative stress in corneas followed by excessive corneal inflammation, neovascularization, and untransparent scar formation. Molecular hydrogen (H2), a potent reactive oxygen species (ROS) scavenger, suppresses oxidative stress and enables corneal healing when applied on the corneal surface. The purpose of this study was to examine whether the H2 pretreatment of healthy corneas evokes a protective effect against corneal alkali-induced oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
(57 reference statements)
0
15
0
2
Order By: Relevance
“…An institutional investigation found evidence that the H2 condition for Figure 3B has been duplicated from Figure 5C of an article previously published by Cejka et al (2016) 1 and the day 4 H2 condition for Figure 4A has been duplicated from Figure 3 of an article published later by Cejka et al (2020) 2 . The authors have not been able to provide all the relevant raw data on request.…”
mentioning
confidence: 92%
“…An institutional investigation found evidence that the H2 condition for Figure 3B has been duplicated from Figure 5C of an article previously published by Cejka et al (2016) 1 and the day 4 H2 condition for Figure 4A has been duplicated from Figure 3 of an article published later by Cejka et al (2020) 2 . The authors have not been able to provide all the relevant raw data on request.…”
mentioning
confidence: 92%
“…Further, it has been well documented that alkali burns promote the accumulation of reactive oxygen species (ROS) in the cornea 24–27 . Following a severe corneal injury, oxidative stress could lead to an antioxidant/prooxidant imbalance in corneal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity has retracted the article titled “An Immunohistochemical Study of the Increase in Antioxidant Capacity of Corneal Epithelial Cells by Molecular Hydrogen, Leading to the Suppression of Alkali-Induced Oxidative Stress” [ 1 ], due to concerns with the figures. The journal was contacted by a reader who identified that Figure 4(j) in [ 1 ] is duplicated with Figure 5(c) in [ 2 ], and Figure 5(a) in [ 3 ]. Additionally panel 4 of Figure 3 in [ 1 ] is duplicated with the H2, Day 4 panel of Figure 4(a) in a now retracted article [ 4 ].…”
mentioning
confidence: 99%
“…The journal was contacted by a reader who identified that Figure 4(j) in [ 1 ] is duplicated with Figure 5(c) in [ 2 ], and Figure 5(a) in [ 3 ]. Additionally panel 4 of Figure 3 in [ 1 ] is duplicated with the H2, Day 4 panel of Figure 4(a) in a now retracted article [ 4 ].…”
mentioning
confidence: 99%